Green building technologies as a part of architecture students’ workshops - Kuc Sabina (Technical Transactions)
The purpose of this article is to present how green building technologies impacted contemporary architectural design during students’ architectural workshops, using selected examples. The analysis covers a series of student workshops, conducted in collaboration between the Faculty of Architecture and Construction at L.N. Gumilov Eurasian National University (FAC-ENU) in Astana, Kazakhstan, and the Faculty of Architecture at Cracow University of Technology (FA-CUT), Kraków, Poland. The first part of the workshop, presented under the working title Conceptual Landscape Project of the ENU Recreation Space in Astana, focuses on conceptual design. The main part of the workshop centres on the theme Restoration of the Urban Environment of Madrid: Designing a Multi-Comfort House Saint-Gobain, emphasizing a personality-oriented approach and components of creative independence. The final part describes a student workshop on the theme Architectural Collage: Transformation of Styles in the New Architecture of Astana. In these three parts, the article demonstrates how ideas related to green building technologies were implemented in the creation of architectural spaces. The general conclusions highlight the role of workshops as an effective method of educating students about green building technologies applied in shaping the built environment.